Testing for inherited thrombophilia and consequences for antithrombotic prophylaxis in patients with venous thromboembolism and their relatives - De Stefano, Valerio; Rossi, Elena (Thrombosis and Haemostasis, 2013)
The clinical penetrance of venous thromboembolism (VTE) susceptibility genes is variable, being lower in heterozygous carriers of factor V Leiden and prothrombin 20210A (mild thrombophilia), and higher in the rare carriers of deficiencies of antithrombin, protein C or S, and those with multiple or homozygous abnormalities (high-risk thrombophilia). The absolute risk of VTE is low, and the utility of laboratory investigation for inherited thrombophilia in patients with VTE and their asymptomatic relatives has been largely debated, leading to the production of several Guidelines from Scientific Societies and Working Groups. The risk for VTE largely depends on the family history of VTE. Therefore, indiscriminate search for carriers is of no utility, and targeted screening is potentially more fruitful. In patients with VTE inherited thrombophilia is not scored as a determinant of recurrence, playing a minor role in the decision of prolonging anticoagulation; indeed, a few guidelines consider testing worthwhile to identify carriers of high-risk thrombophilia, particularly those with a family history of VTE. The identification of the asymptomatic carrier relatives of the probands with VTE and thrombophilia could reduce cases of provoked VTE, offering them primary antithrombotic prophylaxis during risk situations. In most guidelines, this is considered justified only for relatives of probands with a deficiency of natural anticoagulants or multiple abnormalities. Counselling the asymptomatic female relatives of individuals with VTE and/or thrombophilia before pregnancy or the prescription of hormonal treatments should be administered with consideration of the risk driven by the type of thrombophilia and the family history of VTE.
Keywords: Inherited thrombophilia; guidelines; venous thromboembolism; laboratory investigation; familial investigation